The Effect of Different Vegetable Oils on Cedar Wood Surface Energy: Theoretical and Experimental Fungal Adhesion - Bennouna, Fadoua; Sadiki, Moulay; Elabed, Soumya; Ibnsouda Koraichi, Saad; Lachkar, Mohammed (International Journal of Biomaterials, 2022)
Despite having been used for ages to preserve wood against several effects (biological attack and moisture effects) that cause its degradation, the effect of vegetable oils on the cedar wood physicochemical properties is poorly known. Thus, in this study, the hydrophobicity, electron-acceptor (γ+), and electron-donor (γ−) properties of cedar wood before and after treatment with vegetable oils have been determined using contact angle measurement. The cedar wood has kept its hydrophobic character after treatment with the different vegetable oils. It has become more hydrophobic quantitatively with values of surface energy ranged from −25.84 to −43.45 mJ/m2 and more electron donors compared to the untreated sample. Moreover, the adhesion of four fungal strains (Penicillium commune (PDLd”), Thielavia hyalocarpa, Penicillium commune (PDLd10), and Aspergillus niger) on untreated and treated cedar wood was examined theoretically and experimentally. For untreated wood, the experimental adhesion showed a positive relationship with the results obtained by the extended Derjaguin–Landau–Verwey–Overbeek (XDLVO) approach which found that all fungal strains could adhere strongly to the cedar wood material. In contrast, this relationship was not always positive after treatment. The Environmental Scanning Electron Microscopy (ESEM) has shown that P. commune (PDLd10) and A. niger were found unable to adhere to the wood surface after treatment with sunflower and rapeseed oils. In addition, the results showed that the four fungal strains’ adhesion was decreased with olive and linseed oils treatment except that of P. commune (PDLd10) treated with linseed oil.